A Quality of Learning Leadership: Multi-Site Studies - Simatupang , Umy Nadrah; Marsidin, Sufyarma; Rusdinal; Jasrial (Indonesian Research Journal in Education |IRJE|, 2024)
The school principal’s leadership is an essential value in realizing quality education. This research is qualitative and based on a multi-site study. The research results show that the principal of Al Azhar 32 Islamic Junior High School Padang carries out various strategies to improve the school’s quality by having good relationships with parents through approaches in supporting school programs, running programs that will enhance religious and moral values, conducting training for teachers to improve the quality of teaching, and always involving students in competitions. Meanwhile, the principal of Jhons Febby Islamic Junior High School conducts systemic planning and evaluation of school programs, implements open communication with school staff, has superior programs, and strengthens cooperation and collaboration between school staff.